The Responsibilities Between Providing Archipelagic Sea Lanes Passage and Protecting Marine Environment: A Case in Republic of Indonesia - Lestari, Maria Maya (UI Scholars Hub, 2018)
State responsibility in international law is only charged to an independent state. Such responsibility can be created due to the rules of international law regarding the state responsibility and numerous important agreement signatories. Part XII of LOSC 1982 clearly states that “States have the obligation to protect and preserve the marine environment”. On the other hand, agreement might cause the issue of state responsibility, such as archipelagic sea-lanes in Indonesia. The obvious issue has raised serious problem, for instance, overlapping responsibility handled by the government of Indonesia under its implementation. On one side, Indonesia must preserve the marine environment by setting the marine protected areas (MPA). At the same time, Indonesia must ensure the existence of archipelagic sea lanes (ASLs), including its legality for international shipping. This make Indonesia face a dilemma, since its territorial seas also lies withincoral triangle. The recent solution undertaken by the government is prioritizing the existence of ASLs amongst with the rights of cross voyage, taking into account that ASLshave been set out prior to MPAs as well as the recognition of the sovereignty of archipelagic state created at the same time with the obligation of guaranteeing the right of crossing the ASLs. Thus, a plan for designating environmental protection area withASLs, the assignment should not interfere with it. Therefore, to accommodate both interests, The Indonesian government must immediately deliver to the International Maritime Organization (IMO) regarding the condition of marine environment in which ASLP is closely confronted with MPAs to regulate special arrangements when the ships cross the area